2018
DOI: 10.21873/invivo.11452
|View full text |Cite
|
Sign up to set email alerts
|

β-Hydroxy-β-methyl Butyrate/L-Arginine/L-Glutamine Supplementation for Preventing Hand–Foot Skin Reaction in Sorafenib for Advanced Hepatocellular Carcinoma

Abstract: Background/Aim: Sorafenib is standard treatment for advanced hepatocellular carcinoma (HCC). Hand-foot skin reaction (HFSR) is a notorious side-effect of this therapy. This study evaluated prophylactic benefits of an oral nutritional supplement (ONS) on sorafenib-associated HFSR in advanced HCC. Patients and Methods: This was a prospective, singlecenter, open-label trial arm using combined ONS and sorafenib in patients

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(42 citation statements)
references
References 20 publications
1
31
0
Order By: Relevance
“…A beneficial effect of HMB supplementation on reducing serum C‐reactive protein levels was shown in two NRSIs 53,58 ( Figure 2); however, controls receiving glutamine alone presented with greater reductions in this inflammatory marker 53 . Supplementation with HMB/Arg/Gln also had a beneficial effect on tumour response in patients undergoing sorafenib treatment in another NRSI 48 . Compared with historical controls, tumour response rate was similar and a greater disease control rate was found in patients receiving the supplement 48 ( Figure 2).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…A beneficial effect of HMB supplementation on reducing serum C‐reactive protein levels was shown in two NRSIs 53,58 ( Figure 2); however, controls receiving glutamine alone presented with greater reductions in this inflammatory marker 53 . Supplementation with HMB/Arg/Gln also had a beneficial effect on tumour response in patients undergoing sorafenib treatment in another NRSI 48 . Compared with historical controls, tumour response rate was similar and a greater disease control rate was found in patients receiving the supplement 48 ( Figure 2).…”
Section: Resultsmentioning
confidence: 90%
“…Nine NRSIs (60.0%) of varied designs met the eligibility criteria, including a total of 527 patients (mean or median range: 62.3–69.0 years) with diverse cancer types and stages. A supplement containing HMB/Arg/Gln was taken by patients in seven studies 48–53,59 . Of these, one trial 59 prescribed HMB/Arg/Gln in combination with HMB‐enriched ONS for patients with mild or severe protein‐energy malnutrition.…”
Section: Resultsmentioning
confidence: 99%
“…27 In addition, there was another similar trial using combined oral nutritional supplement and sorafenib in patients with HCC, the results suggested that prophylactic HMB, L-arginine and L-glutamine supplementation effectively prevented sorafenib-associated HFSR in patients with advanced HCC. 28 However, these studies only provided some prophylaxis strategies but not the treatment strategy of HFSR. Previous studies showed that modified Taohongsiwu decoction and Compound Danxiong Granules (CDG) could effectively attenuate MKIs-associated HFSR.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Naganuma et al. ( 64 ) found that prophylactic administration of an ONS (oral nutritional supplement) containing these ingredients before the initiation of sorafenib treatment could effectively decrease the incidence of HFSR. Other possible medications include analgesics (e.g.…”
Section: Histology Of Hfsrmentioning
confidence: 99%
“…It has been proved that b-hydroxy-b-methylbutyrate (HMB), Larginine, and L-glutamine could promote collagen synthesis in the process of wound healing. Recently, Naganuma et al (64) found that prophylactic administration of an ONS (oral nutritional supplement) containing these ingredients before the initiation of sorafenib treatment could effectively decrease the incidence of HFSR. Other possible medications include analgesics (e.g.…”
Section: Other Medicationsmentioning
confidence: 99%